Anchoring and Adjustment in Relevance Estimation - Shokouhi, Milad; White, Ryen W.; Yilmaz, Emine (Proceedings of the ACM International Conference on Research and Development in Information Retrieval (SIGIR2015), 2015)
People’s tendency to overly rely on prior information has been well studied in psychology in the context of anchoring and adjustment. Anchoring biases pervade many aspects of human behavior. In this paper, we present a study of anchoring bias in information retrieval (IR) settings. We provide strong evidence of anchoring during the estimation of document relevance via both human relevance judging and in natural user behavior collected via search log analysis. In particular, we show that sequential relevance judgment of documents collected for the same query could be subject to anchoring bias. That is, the human annotators are likely to assign different relevance labels to a document, depending on the quality of the last document they had judged for the same query. In addition to manually assigned labels, we further show that the implicit relevance labels inferred from click logs can also be affected by anchoring bias. Our experiments over the query logs of a commercial search engine suggested that searchers’ interaction with a document can be highly affected by the documents visited immediately beforehand. Our ﬁndings have implications for the design of search systems and judgment methodologies that consider and adapt to anchoring effects.